ASSOCIATION BETWEEN CARDIAC ARRHYTHMIAS, INTRACARDIAC AND CENTRAL HEMODYNAMICS IN PATIENTS WITH POST-INFARCTION CARDIOSCLEROSIS AND MITRAL REGURGITATION - N. A. Volov; O. S. Kuz’menko (Российский кардиологический журнал, 2010)
The study investigated the association between cardiac arrhythmias and hemodynamic parameters in patients with myocardial infarction and mitral regurgitation of varying severity. In total, 70 men (mean age 62 years) were examined, including 35 individuals with cardiac arrhythmias. Left ventricular (LV) systolic and diastolic myocardial function, arrhythmia characteristics, and mitral regurgitation severity were assessed. A significant decrease in LV ejection fraction and more advanced diastolic dysfunction was observed in patients with ischemic mitral regurgitation and cardiac arrhythmias. In this group, patients with severe mitral regurgitation demonstrated ventricular extrasystoles of high Lown classes. Therefore, mitral regurgitation progression and subsequent diastolic dysfunction could be associated with higher risk of ventricular arrhythmias.